PHYSICAL ACTIVITY AS A LEADING FACTOR, DETERMINING THE HEALTH STATUS AND QUALITY OF LIFE OF URBAN RESIDENTS - Чобанов Р. Е.; Ісламзаде І. Ф. (World of Medicine and Biology, 2016)
Goal. Assessment of physical activity (PA) as the leading factor determining the health status and quality of life of urban residents in terms of hyperurbanization. Methods. The work carried out on the bases of 3 health centers in Baku and geographically associated in 3 high schools, 5 kindergartens and nurseries. Processed 1819 questionnaires, compiled on bases of the international questionnaires SF-36, GPAQи Moreesky filled with patients of the clinics, parents, children’s agencies and employees of nearby commercial facilities and offices. The questionnaire reflected the socio-hygienic aspects of low PA. Also analysed the hospital records of respondents. Results. Modern intensive pace of life of adults in terms of hyperurbanization (the service, the family and ensuring its development, upbringing and education of children and much more) leaves no time not only for active sports but also for normal activities and sleep. In our study the special physical activity engaged in from 1829 176 respondents (9,6±0,7%), and 131 of them were younger than 35 years. The only physical activity the rest are walking - on service, children’s institution, commercial properties. Considered when PA is less than 30 min/day of moderate walking, the body is not getting needed exercise, when walking in the range of 30-60 min/day this load is minimal, and walking more than 60 min/day it is sufficient. F even in such an accessible form without requiring extensive time and effort, including daily moderate walking, the majority of respondents was very low. PA within < 30 min/day was observed in 52,6±1,2%, in the range of 30-60 min/day to 28.6±1.1% in the range of > 60 min/day at 18,8±0,9% of respondents. Low physical activity contributes to the formation of somatic symptoms - an average of 5.03±0.29 1 symptoms on the questionnaires. A good level of self-rated health does not exceed 21,5±1,0%. The quality of life of respondents below satisfactory level and is an average of 48.9±1.6 points. Sufficient awareness on the problems PA does not exceed 31,5±2,5%. Conclusions. The process of hyperurbanization and lack of awareness contribute to a wide dissemination among the urban residents of low physical activity, which has aggravating effects on their health and quality of life. Conducted organizational training on awareness of urban residents relative to PA contributed to their physical activation.